Webster's concise encyclopedia (Las Cruces, N.M. Sofsource)
Contains over 20,000 entries, 2,500 illustrations, interactive audio and video, a time line of history, and world atlas.
System requirements: IBM PC or compatible with a CD-ROM drive running any of the following: Windows 3.1, Windows 3.11, Windows 95.
Keywords: Encyclopedias and dictionaries